IMPLEMENTATION OF DIFFERENTIATED LEARNING IN IMPROVING STUDENTS' LEARNING SUBJECTS RESULTS AT SDN 2 KARANG LUHUR - Moutawaqil, Nawal El; Susanto, Moh. Rusnoto (Yayasan Education and Social Center, 2024)
This community service activity aims to improve student learning outcomes in the Arts, Culture, and Stage Basics (SBDP) subjects at SDN 2 Karangluhur by implementing differentiated learning. The research subjects consisted of 33 fifth-grade students, with a ratio of 20 female students and 13 male students. The observations and questionnaires showed significant variations in students' multiple intelligences, with 39% being visually spatially intelligent, 12% being kinesthetically intelligent, and 48% being musically intelligent. Teachers apply differentiated learning strategies to overcome these intelligence differences and increase student interest and participation. The initial mapping of students' multiple intelligences is the basis for giving students the freedom to choose roles in the performing arts. Observation results show increased students' active and total participation in the performance, creating an inclusive learning environment that embraces diversity. Differentiated fine arts learning is a practical approach to overcoming obstacles and increasing student interest and participation in fine arts learning at the elementary level. This approach pays attention to students' multiple intelligences and provides space for students' creativity and personal expression in the context of inclusive learning. This activity's results can positively contribute to the quality of fine arts learning in elementary schools and stimulate students' creative potential and expression